Changing Occurrences of Fall Blooms Associated With Variations in Phytoplankton Size Structure in the Pacific Arctic - Waga, Hisatomo; Hirawake, Toru (Frontiers in Marine Science, 2020)
Phytoplankton blooms in the Pacific Arctic have been characterized as a huge single bloom in spring. However, several studies have reported recent increases in the occurrence of fall blooms during the period after dissipation of the spring bloom. Here, we explored spatiotemporal variations in the occurrence of fall blooms in the region, using satellite remote-sensing data for 2003–2017. Seasonal time-series variation in satellite-derived chlorophyll-a concentrations (chla) was modeled using a Gaussian function to distinguish whether a peak in chla was evident in fall; an occurrence of a fall bloom was recognized if the model detected the presence of a chla peak in fall. In addition, phytoplankton size structure was estimated from the satellite data to examine the influence of fall blooms on seasonal variations in the size structure. The results indicate that fall blooms occurred in a wide area of the Pacific Arctic, and larger phytoplankton were predominant during fall blooms relative to the phytoplankton present before/after the bloom or in the absence of a fall bloom. Examining interannual variation in occurrences of fall blooms revealed clear increasing and decreasing trends in the southern Chukchi Sea and the St. Lawrence Island polynya region, respectively, possibly associated with temporal variations in atmospheric forcing as well as in the water-column structure. Because the cell sizes of phytoplankton largely determine their sinking rate, temporal trends in the occurrence of fall blooms modulating seasonal variations in phytoplankton size structure could significantly influence marine ecosystems. These results suggest that spatiotemporal monitoring of phytoplankton communities not only in spring but also after the period or their dissipation would improve our understanding about processes causing variations within marine ecosystems, as might occur in the Pacific Arctic.